A coproduction research model between academia and law enforcement responsible for investigating threats. Issue 1 (2nd January 2021) - Silver, James M.; Craun, Sarah W.; Wyman, John V.; Simons, Andre B.
ABSTRACT: Academics and law enforcement practitioners engage in collaborative studies, driven both by individual efforts and government support, and have developed several models of cooperation that hold promise for continued partnership. In this article, we present an example of one collaborative model – coproduction – involving a federal law enforcement agency and an academic studying threat assessment and the behaviours of violent offenders in the United States. Our focus is not on the findings from the underlying research; rather we describe and reflect on the process itself, outlining the benefits as well, as the pitfalls, for both law enforcement and academics. Our overall experience provides a realistic picture of how these partnerships can be responsive to the needs and aims of both parties, to the advantage of the research.